Broken vessel - Ross, Kate (New York, N.Y., U.S.A. : Penguin Books, 1995)
In 1820's London, Julian Kestrel and an unlikely partner--bold and bewitching prostitute Sally Stokes--stalk a murderer through the high places and low life in Regency London, after Sally mistakenly steals a letter from one of her clients containing an urgent plea for help from a distraught young woman
"A Julian Kestrel mystery"--Cover.
78323
Keywords: Kestrel, Julian (Fictitious character) -- Fiction; London (England) -- Fiction; Mystery fiction; Historical fiction